Tumor immune microenvironment changes are associated with response to neoadjuvant chemotherapy and long-term survival benefits in advanced epithelial ovarian cancer: A pilot study - Cao, Guangming; Hua, Dingchao; Li, Jinfeng; Zhang, Xuefang; Zhang, Zhiqiang; Zhang, Bei; Bei, Ting; Cui, Lina; Chen, Shiqing; Wang, Shuzhen; Zhu, Lei (Frontiers in Immunology, 2023)
In advanced and metastatic epithelial ovarian cancer (EOC) where complete resection is not feasible, neoadjuvant chemotherapy (NACT) followed by interval debulking surgery (IDS) and adjuvant chemotherapy is an alternative. However, the 5-year survival is still only around 30%. Increasing clinical evidence has suggested that analyses of tumor immune environment (TIME) of treatment-naïve tumor has allowed for identifying components of immune contexture that are beneficial or deleterious to ovarian cancer patients. Little is known about the association of the dynamic change of TIME during treatment with the efficacy of NACT and survival in EOC. This study investigated the TIME landscape of treatment-naive EOC tumors using multiplex immunofluorescence and associated the TIME before and after platinum-based NACT with treatment efficacy and prognosis in 33 patients with advanced EOC. NACT significantly increased the density of CD8+ T cells (P = 0.033), CD20+ B cells (P = 0.023), CD56 NK cells (P = 0.041), PD-1+ cells (P = 0.042), and PD-L1+CD68+ macrophages (P = 0.005) in the tissue specimens. Response to NACT was evaluated using CA125 response and chemotherapy response score (CRS). Compared with the non-responders, the responders displayed a larger proportion of tumors showing increase in the infiltration of CD20+ B cells (P =0.046) and in the M1/M2 ratio (P =0.038) as well as fewer tumors showing increase in the infiltration of CD56bright cells (P =0.041). No association was found between pre-NACT TIME and response to NACT. Density of pre-NACT CD8+ cells was positively associated with longer progression-free survival (PFS) (P =0.011) and overall survival (OS) (P =0.048). Post-NACT CD20+ cells and CD163+ macrophages (M2) infiltrates were associated with prolonged (P =0.005) and shortened PFS (P =0.021), respectively. Increase in the density of CD4+ T cells was predictive for longer PFS (P =0.022) and OS (P =0.023). In the multivariate analysis, high density of CD8+ cells pre-NACT (P =0.042) were independently associated with improved OS.